Climate change and floods in Yemen: Impacts on food security and options for adaptation - Wiebelt, Manfred; Breisinger, Clemens; Ecker, Olivier; Al-Riffai, Perrihan; Robertson, Richard D.; Thiele, Rainer (International Food Policy Research Institute, 2011)
This paper uses both a global and local perspective to assess the impacts of climate change on the Yemeni economy, agriculture, and household income and food security. The major impact channels of climate change are through changing world food prices as a result of global food scarcities, long-term local yield changes as a result of temperature and rainfall variations, and damages and losses of cropland, fruit trees, livestock, and infrastructure as a result of natural disasters such as recurrent storms and floods. Moreover, spatial variation in climate change impacts within Yemen means that such effects can vary across subnational regions. We develop a recursive dynamic computable general equilibrium (DCGE) model with six agroecological zones to capture linkages between climate change, production, and household incomes. We also capture changes in per capita calorie consumption in response to changing household expenditure for assessing changes in people's hunger situation as a measure for food security. Given the high uncertainty surrounding future global food prices and local yields, all simulations are run under two global climate scenarios. The results of the CGE simulations suggest that climate-change-induced higher global prices for food will lower Yemen's overall GDP growth, raise agricultural GDP, decrease real household incomes, and increase the number of hungry people. Local impacts of climate change are different for the two climate scenarios. Overall, the long-term implications of climate change (local and global) lead to a total accumulated reduction of household welfare of between US$5.7 and $9.2 billion by 2050 under MIR or CSI conditions, respectively. Moreover, between 80,000 and 270,000 people could go hungry due to climate change. Rural households are harder hit than urban households, and among the rural households the non-farm households suffer most. This household group is projected to lose an accumulated 3.5 to 5.7 billion US$ as a consequence of longer term climate change by 2050. In addition to the longer-term climate change effects, climate variability is shown to induce heavy economic losses and spikes in food insecurity. The impact assessment of the October 2008 tropical storm and floods in the Wadi Hadramout puts the total cumulated real income loss over the period 2008-12 at 180 percent of pre-flood agricultural value added. Due to the direct flood loss, farmers in the flooding areas suffer most in the year of the flood occurrence, where the percentage of hungry people living from farming spiked by about 15 percentage points as an immediate result of the flood. Action to mitigate the negative effects of climate change and variability should to be taken on the global and local level. A global action plan for improving food security combined with a better integration of climate change in national development strategies, agricultural and rural policies, and disaster risk management and social protection policies will be keys for improving the resilience of Yemen and Yemenis to climate change.